Setting the appropriate tax on cigarettes in Ireland - David Madden (University College Dublin, Department of Economics, 2002)
This paper examines the issues involved in setting the appropriate tax on cigarettes in Ireland. It compares Irish tax rates with those in other EU countries and then examines the external costs of cigarette consumption in Ireland. The paper concludes by reviewing some recent evidence that smokers do not fully take on board the internal costs of cigarette consumption which in turn could have major implications for appropriate levels of tax.
hdl:10197/764
Keywords: 330; Tabaksteuer; Optimale Besteuerung; Irland